KELAYAKAN VIDEO PEMBELAJARAN BERBASIS PLATFORM YOUTUBE PADA MAKANAN PEMBUKA (HOT DAN COLD APPETIZER) TERHADAP PEMAHAMAN SISWA - Ayu Indah Mawarni; Mauren Gita Miranti; Lucia Tri Pangesthi; Ita Fatkhur Romadhoni Romadhoni (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Learning media is related to anything that can be used to convey information in the teaching and learning process so that it can stimulate attention to learning. This study aims to analyze learning videos for appetizers (hot and cold appetizers) in order to find out how appropriate learning videos are used by students and their effect on student understanding in class XI Cullinary at SMK Negeri 2 Jombang taken by random sampling technique. .This study uses a mixed method research type (qualitative and quantitative). Data collection techniques using pre test and post test. The results of the video analysis show that the video that has the highest average feasibility value is video 2 with the title KD.3 Analyzing the appetizer with a percentage of 80% which is then tested on class XI Cullinary. The results of the normality test stated that the pre-test and post-test data in this study were normally distributed because with the Kolmogorov-Smirnov it was known that the exact sig pre-test value obtained 0.11> 0.05 and post-test 0.06> 0.05. found the number 0.56 with df 1 is worth 1 and df2 is worth .120 with a significance level of 0.56 > 0.05 so that the conclusion is that the data is homogeneous. .Hypothesis T test based on the results of the pre-test and post-test using the Kolmogorov Smirnov method states 0.00 <0.05, which means it can be concluded that the use of learning media based on the YouTube platform with the title KD.3 Analyzing appetizers has an influence on student understanding Class XI Cullinary at SMKN 2 Jombang.